Correlation between remnant cholesterol and premature coronary artery disease and the severity of coronary artery lesions in men: a retrospective study - Dong, Xingming; Chen, Ke; Li, Xiuqin; Tang, Yuanyuan; Zhang, Rui; Wang, Jian (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveTo investigate the correlation between remnant cholesterol (RC) and premature coronary artery disease (PCAD) and the severity of coronary artery lesions in men.MethodsA total of 630 male subjects who underwent coronary angiography were included in the study. The general data, laboratory tests, and coronary angiography data of each group were statistically analyzed, and RC levels were calculated. According to the Gensini score, PCAD was divided into mild and severe lesion groups. The relationship between RC and PCAD and coronary artery lesions was analyzed using multivariate logistic regression and spearman correlation analysis, and the predictive value of RC for coronary artery lesions was evaluated using receiver operating characteristic (ROC) curves.ResultsThe RC levels in the PCAD group were significantly higher than those in the non-PCAD group (p < 0.05), and RC was an independent risk factor for PCAD (p < 0.05).The RC levels in the severe lesion group were higher than those in the mild lesion group (p < 0.05), and RC levels were positively correlated with the Gensini score (r = 0.335, p < 0.001).Multivariate logistic regression analysis showed that RC was an independent risk factor for severe coronary artery lesions (p < 0.05).The ROC curve calculated the value of RC in predicting severe coronary artery lesions, with an area under the curve of 0.693, a cutoff value of 0.485 mmol/L, a sensitivity of 64.7%, and a specificity of 66.2%.ConclusionRC is an independent risk factor for PCAD and the severity of coronary artery lesions in adult men. RC levels are positively correlated with the severity of coronary artery lesions and can be used as an auxiliary indicator for clinical assessment of PCAD.